2007
DOI: 10.3177/jnsv.53.53
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Ceramide in the Liver and Plasma after Carbon Tetrachloride Intoxication in the Rat

Abstract: SummaryIn fulminant hepatic failure, various toxins causing multi-organ failure increase in plasma. As a novel toxin, levels of ceramide, a well-studied lipid mediator of apoptosis, were determined by LC-MS/MS in the liver and plasma of carbon tetrachloride (CCl 4 )-intoxicated rats. After 6 h of oral administration of CCl 4 (4 mL/kg body weight as a 1 : 1 mixture of CCl 4 and mineral oil) to rats, extensive hepatic failure occurred as evidenced by a severe elevation in plasma AST and ALT. The liver concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
0
27
2
Order By: Relevance
“…Considering the lower resonance of 128MHz at 3T and the observation of broad baseline positive MTR asym peak above 1.5ppm (blue curves in Figs 3b and 4b), it is possible that – NH has concomitant spill-over effects at higher chemical shifts and induces positive MTR asym . On the other hand, it was found by Ichi et al [45] that ceramide in the liver and plasma increased after CCl4 intoxication in the rat. It seems conflicting with the reduction of APTw MTR asym observed in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Considering the lower resonance of 128MHz at 3T and the observation of broad baseline positive MTR asym peak above 1.5ppm (blue curves in Figs 3b and 4b), it is possible that – NH has concomitant spill-over effects at higher chemical shifts and induces positive MTR asym . On the other hand, it was found by Ichi et al [45] that ceramide in the liver and plasma increased after CCl4 intoxication in the rat. It seems conflicting with the reduction of APTw MTR asym observed in our study.…”
Section: Discussionmentioning
confidence: 92%
“…A series of studies have shown that increased ceramide levels in both liver and plasma coincide with the development of liver dysfunction, hepatic insulin resistance, and steatosis in rodents (Ichi et al, 2007; Xia et al, 2014; Yetukuri et al, 2007). Previous work has identified the liver as a target of ceramide-induced insulin resistance and inhibition of whole-body ceramide synthesis reduces obesity-induced insulin resistance in rodents (Holland et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While some of these approaches may be used to analyze total ceramide, they do not provide data on individual ceramide species [15, 21]. In addition, existing methods provide discrepant results for ceramide levels in different biological samples [22–24]. Recent developments in electrospray ionization tandem mass spectrometry (ESI-MS/MS) have helped resolve some of these limitations.…”
Section: Introductionmentioning
confidence: 99%